Preexposure and Postexposure Prophylaxis of Rabies With Adeno-Associated Virus Expressing Virus-Neutralizing Antibody in Rodent Models - Huang, Fei; Ren, Meishen; Pei, Jie; Mei, Hong; Sui, Baokun; Wu, Qiong; Chai, Benjie; Yang, Ruicheng; Zhou, Ming; Fu, Zhen F.; Zhou, Huiping; Zhao, Ling (Frontiers in Microbiology, 2021)
Rabies, a fatal disease in humans and other mammals, is caused by the rabies virus (RABV), and it poses a public health threat in many parts of the world. Once symptoms of rabies appear, the mortality is near 100%. There is currently no effective treatment for rabies. In our study, two human-derived RABV-neutralizing antibodies (RVNA), CR57 and CR4098, were cloned into adeno-associated virus (AAV) vectors, and recombinant AAVs expressing RVNA were evaluated for postexposure prophylaxis after intrathecal injection into RABV-infected rats. At 4days post-infection with a lethal dose of RABV, 60% of the rats that received an intrathecal injection of AAV-CR57 survived, while 100% of the rats inoculated with AAV-enhanced green fluorescent protein (EGFP) succumbed to rabies. Overall, these results demonstrate that AAV-encoding RVNA can be utilized as a potential human rabies postexposure prophylaxis.